Exotic h → Za Higgs decays into τ leptons - M. Cepeda; J. M. No; C. Ramos; R. M. Sandá Seoane; J. Zurita (Journal of High Energy Physics)
Abstract Exotic Higgs decays are among the most promising areas to be explored at the High-Luminosity LHC, given the unprecedentedly large amount (~ 3 × 108) of 125 GeV Higgs bosons that will be produced. In this context, we propose a new search channel for which the Higgs boson decays to a (leptonically decaying) Z boson and a light BSM pseudoscalar a, which subsequently decays to a pair of τ-leptons (h → Za → ℓℓττ). After performing a validation of existing ATLAS and CMS exotic Higgs decay searches in related channels, we analyze the HL-LHC projected sensitivity of our a → ττ search, targeting the kinematic region where the exotic Higgs decay is two-body. We are able to probe pseudoscalar masses m a ∈ [5, 33] GeV by leveraging both leptonic and hadronic τ decays, and establish model-independent 95% C.L. sensitivity projections on the branching fraction BR(h → Za) × BR(a → ττ). These a → ττ projections yield a competitive probe of light pseudoscalars, which depending on the model can become significantly more sensitive than projections from existing experimental searches in a → μμ and a → γγ final states. Finally, we explore the potential of our search to probe an Axion-Like-Particle (ALP) solution to the muon (g − 2) anomaly (when taken face-value), finding that our proposed h → Za, a → ττ search can provide valuable constraints on such ALP scenario, in complementarity with existing h → Za, a → γγ experimental searches.